The Role of Investigators in Ensuring Criminal Mediation Compliance in Restorative Justice - Hardista Pramana Tampubolon (Transpublika Publisher, 2026)
The Indonesian criminal justice system is currently still dominated by a retributive approach, which tends to neglect victim recovery and social relations. As an alternative, restorative justice has been introduced to resolve criminal cases through penal mediation between perpetrators and victims. However, in practice, many mediation agreements are not implemented (breach of contract), threatening the effectiveness of restorative justice. This study aims to analyse the role of investigators from the General/Jatanras Sub-Directorate of the Metro Jaya Regional Police Criminal Investigation Directorate in preventing the failure to implement peace agreements in the penal mediation process. The method used is normative-empirical legal research with a qualitative approach. Data collection techniques included interviews, observation, and documentation, with data analysis using the Miles and Huberman technique and triangulation verification. The results of the study show that investigators play an active role as facilitators, mediators, agreement drafters, and supervisors of the implementation of agreements. Investigators also play a preventive and repressive role in anticipating default, and contribute to victim recovery by creating a safe and supportive space for dialogue. This study concludes that the success of restorative justice is highly dependent on the capacity and integrity of investigators in ensuring that peace agreements are fully implemented. The uniqueness of this study lies in its emphasis on the substantive role of investigators in bridging legal values and social needs, as well as filling the normative void in the supervision of the implementation of penal mediation.